BEING INVOLVED OR INFORMATIVE: GENDER DIFFERENCES IN THE USE OF PRONOUNS AND SPECIFIERS IN WRITING CONCLUSIONS - Dian Agustina Purwanto Wakerkwa (UIN Raden Mas Said Surakarta, 2023)
The conclusion comprises the summary of the study. It is where the authors present their last words about the findings while introducing some suggestions on the issue. Gender is believed to be one of social factors that shapes someone’s communication style, be it oral or written. This study aimed to explore the differences in the use of pronouns and noun specifiers by authors of different genders in composing the conclusions of their research articles. It observed how pronouns and specifiers are manifested differently in the texts and the different intentions behind their use. Ten research articles’ conclusions were randomly selected based on gender of the authors five of each gender from one Indonesian journal in the field of language study. This study is qualitative, thus, the data are analyzed and presented in words to a draw clear interpretation of the issue. The findings revealed the differences in the tendency of female and male authors in utilizing both linguistic features in the conclusions. It was discovered that female authors utilized more pronouns and male authors, on the other hand, used more noun specifiers in their texts.